Evaluación del desempeño de filtración en múltiples etapas usando carbón activado granular y mantas sintéticas no tejidas - Tangerino, Edson Pereira [UNESP]; Araujo, Laryssa Melo Rosa [UNESP]; Borges, Rívea Medri [UNESP]; Ortiz, Iván Andrés Sánchez (My University, 2013)
The multi stage filtration (MSF) is an alternative that permits to enlarge the spectrum of application of the slow sand filtration as for the effluent quality and run duration. In this research the use of MSF technology associated to a granular activated carbon (GAC) column as polishing mechanism of the final effluent was evaluated; in the slow sand filters GAC was used as an intermediate layer and non-woven synthetic fabrics were utilized as a first layer of the filter media. Five different tests were conducted, where the systems subjected to the treatment were: water from the Ipe Lake (Ilha Solteira, Sao Paulo, Brazil); water from the lake with water from a recreational fish pond; water from the lake with a phytoplankton and cyanobacteria overload simulation, with and without the use of the pre-filters as a stage of the treatment. The synthetic fabrics and GAC use resulted in the best turbidity removal and an efficient apparent and true color removal; in spite that the polishing columns reported similar results for those parameters. The utilization of GAC as an intermediate layer contributed to a better organic matter removal and the fabrics improved chlorophyll-a removal. The pre-filtration columns made an efficient algae and cyanobacteria removal, a function that was completed by the filters and reached >98% efficiency. The synthetic non-woven fabrics and GAC inclusion in MSF operation improved performance of this technology with ease of application and operation.
Performance evaluation of multi-stage filtration with use of granular activated carbon and synthetic non-woven fabrics